Studi Karakteristik Petani Desa Tulungrejo dalam Mendukung Pengembangan Agrowisata “Bon Deso” - Pravasta Wahyu Satriawan; Muhammad Saikhu; Rika Despita; Budi Sawitri (Fakultas Pertanian Universitas Jember, 2021)
This study aims to study the support characteristics of Tulungrejo Village Farmers for the development of